The Impact of Adopting and Using Technology by Children - Hind Talal Mashrah (Intelektual Pustaka Media Utama, 2017)
Nowadays, information communication technology is becoming an essential part of our life. We find technology everywhere to facilitate teaching and learning, especially in schools and homes. It always comes along with interactive and interacting approaches to help children learn math and science and so on. This paper, however, discusses the downside effects of using technology to children from age 2 to 17 years old. There are some earlier studies with some statistics indicate the percentage of children who use different kinds of technology in their daily life. Then the paper will be demonstrated the social, cognitive, and physical impacts of using too much technology. Then it will be specified three types of technology as it is common among children: playing video games, surfing websites, and communicating via the internet. Finally, some regulations and guidance are mentioned to protect children throughout giving them better methods to use technology in proper ways and involving children in social, cognitive, and physical activities alongside.